Inverse Matrix RSLPFLcircfr (0,1/b,0) of Order 3×3 to the Power of Positive Integer Using Adjoin Method - Rahma, Ade Novia; Wulanda, Velyn; Rahmawati, Rahmawati; Marzuki, Corry Corazon (Jurusan Matematika, Fakultas Sains dan Teknologi, UIN Sunan Gunung Djati Bandung, 2023)
The matrix RSLPFLcircfr is a particular form of the circular matrix RSLPFLcircfr . This study aims to determine the general form of the inverse matrix RSLPFLcircfr to the power of positive integers. This research begins by determining the general form of the power of the matrix RSLPFLcircfr which is then proven by using mathematical induction. Next, predicting the determinant of the power of the matrix RSLPFLcircfr which is then continued by proving the form generalization of the determinant of the power of the matrix RSLPFLcircfr by direct proof using cofactor expansion. Furthermore, by determining the cofactor matrix of the power of the matrix RSLPFLcircfr we will obtain the inverse of the matrix to the power of the matrix RSLPFLcircfr using the adjoin method.